COMPUTER SOFTWARE AIDED PHOTOCATALYTIC DEGRADATION OF VAT YELLOW DYE USED IN LEATHER AND TEXTILE INDUSTRIES - Olabode Victor O.; Alogala J.A.; Jinaidu Haruna M.; Okon U.E; Jahkeng Williams E (Journal CleanWAS)
This research investigated design of experiment for the optimization of the experimental parameters of the photocatalytic degradation of VAT yellow dye using dye concentration (mg/L), catalyst dosage (mg/L), pH and time of exposure (minates) as experimental factors. Stock solution of vat yellow dye was prepared (0.00001M) and serial dilution was used to prepare twenty seven (27) different concentrations of the dye solution which were subjected to photocatalytic degradation in a photo reactor using a ultraviolent light source under ambient environmental condition. The absorbances of these solutions before and after photo degradation were taken to obtain different percentage degradation for each experimental run. Analysis of these results was carried out using minitab18 computer software. The result revealed the best conditions for the photodegredation as (20mg/l) (dye concentration), 2(mg/L) (catalyst dosage), 3.39 pH and 45 minutes (time of exposure). This was confirmed experimentally after the optimization to prove that minitab18 software is highly effective for the optimization of photodegradation of tannery and textile effluent containing reactive red dye.